An ASEAN Transboundary Haze Court: Why Does it Matter and How is it Possible? - Kusniati, Retno; Helmi, Helmi; Rapik, Mohamad; Permatasari, Bunga; Jaderojananont , Peerapon (Universitas Negeri Semarang, 2024)
As a form of state responsibility as required by the ASEAN Agreement Transboundary Haze Pollution (AATHP), Indonesia and Thailand have provided sanctions to be imposed to the perpetrators of the forest and land fires. However, the national laws or legal instruments on this matter work only domestically and fail to overcome the effect of the domestic forest and land fires which potentially produce transboundary haze pollution. This paper proposes that the ideas of soft law of the AATHP and the non-intervention of the ASEAN Way should be reconsidered in dealing with transboundary haze pollution and a special regional court has to be made as a central authority to impose sanction upon the perpetrators of forest and land fires that cause the transboundary haze pollution. Using a comparative case study, this article evaluates the state responsibility and the implementation of the AATHP ideas in Indonesia and Thailand and put forward the arguments and the possibilities for installing a special court for transboundary haze pollution. The results demonstrate that, due to its regional needs and institutional and legal norms, ASEAN needs a different model of regional court compared to Uni-European’s one.